AN ANALYSIS OF HUMOR OF STUDENTS CHITCHAT PAGE ON FACEBOOK WITHIN COOPERATIVE PRINCIPLE FRAMEWORK: A CASE STUDY ON THE STUDENTS GROUP PAGE - Agnes Arum Budiana; Pretti Ristra; Doris Sukma; Ari Satria (Politeknik Negeri Bengkalis, 2023)
The cooperative principle proposes four maxims in communication. They are the maxims of Quantity, Quality, Relation and Manner. When any of the four maxims is violated or flouted, misunderstanding or implicature, and thus humor might be generated. This study attempts to describe theories in this framework to analyze the maxims violation on studentsâ€™ humor of Students. This is a case study on sophisticated issue in the Students Group Page. It used qualitative study method to generate in-depth understanding about humor of Students Chitchat Page on Facebook through observing the humor which contradicts with the common sense. In Students Chitchat Page on Facebook the four maxims are flouted, violated, infringed, opted out or suspended, so that one remark of humor after another is created.Â Keywords: Cooperative Principle, Humor, Maxims.